The influence of motivation, work discipline and rotation on the performance of micro credit marketers at bank BRI Singaraja - Wayan Agus Parta Sumarta; I Nengah Suarmanayasa; Ni Made Suci (Jurnal Ekonomi, 2024)
The purpose of this study is to ascertain how two or more factors interact. The research location is Bank BRI Singaraja. The subjects in this research were micro credit marketers at Bank BRI Singaraja. The object of this research is motivation, work discipline, rotation on performance. Purposive sampling was employed to choose the 84 participants that made up the study's sample. A Google Form is used to complete a questionnaire as part of the data collecting strategy. This research uses regression analysis methods for figuring out how the independent and dependent variables are causally related. The research results show: (1) The relationship between performance (Y) and motivation (X1). The incentive variable (X1) has a t value of 1.571 according to the t test findings, which is less than the t table value of 1.633. It can be said that motivation (X1) has a negative impact on performance (Y). This means that lower motivation means less performance produced by employees. (2) Evaluating the importance of work discipline's impact (X2) on output (Y). The work discipline variable (X2) has a t value of 1.511 according to the t test findings, which is higher than the t value of 1.633 in the table. Therefore, it can be concluded that performance (Y) is positively and significantly impacted by work discipline (X2). This implies that an employee's performance level will improve with increased job discipline. (3) In order to determine the importance of the rotation (X3) influence on performance (Y), the t test findings indicate that the rotation variable (X3) has a t value of 6.402, which is more than the t value of 1.633 in the table. Job rotation (X3) is proven to be positive and important for performance (Y). This means that employees with regular rotation have a higher level of performance.